ANALYSIS OF THE ROLE OF EDUCATION PERSONNEL IN SCHOOL ADMINISTRATION - Waziana, Winia; Andewi, Widi; Suningsih, Sri (JLCEdu (Journal of Learning and Character Education), 2022)
Educators and education staff have the same role and task, namely carrying out various activities that lead to the creation of convenience and success for students in learning. The role of educators in facilitating school administration is very important because they have great duties and responsibilities for the smooth running of teaching and learning activities in schools. Every school requires skilled, reliable educators, and understand the job description. The formulation of the problem in this paper is first, what is included in school administration? Second, what is the role of education personnel in school administration? The purpose of this study is to increase understanding of the concept of school administration and the professional ethics of education personnel in school administration. This study uses a qualitative method with a library research approach. Data collection techniques by taking data in the library, reading, taking notes, and processing research material. Based on the results of the data analysis, several conclusions were found as follows regarding matters covered in school administration, namely 1. Curriculum Administration, 2. Student Administration, 3. Infrastructure Administration, 4. Financial Administration and 5. Public Relations Administration. The role of education personnel in school administration is to play an active role in quality service efforts, and the formation of professional human resources in the field of school development and administration. As well as carrying out the educational code of ethics as a form of moral responsibility towards his profession as an educator